Authentic leadership : an engaged discussion of LGBTQ work as culturally relevant - Watson, Lemuel W.; Johnson, Joshua Moon (Emerald Publishing Limited : Information Age Publishing, Inc., 2013)
This book provides new insights about the roles in which LGBTQ individuals contribute in society and various organizations. The literature is divided into two sections. Section one includes three chapters from higher education administrators, faculty and community activists. The chapters share personal narratives describing the life experiences of those who are often marginalized within academia. Each chapter provides personal and professional aspects of the authors' lives. Section two includes four chapters which, shares voices of people whom are normally excluded from research. Each author's identity is shared as an aspect of their research.The authors present a broad range of issues, challenges and concerns, supported by prior literature, organized around several broad topical areas and intended to fill the gaps in our knowledge about how LGBTQ leadership is engaged across multiple types of institutions and how the experiences affect the quality of life for LGBTQ individuals throughout the academic community. Their complex identities affect their research interests, findings, and interpretations.
Keywords: Homosexuality.; Leadership.; Homosexuality in the workplace.; Business & Economics -- Leadership.; Relating to LGBTQ+ people.; Management: leadership and motivation.; elektronické knihy; electronic books